1999
DOI: 10.1038/sj.bdj.4800116
|View full text |Cite|
|
Sign up to set email alerts
|

Canalis sinuosus mimicking a periapical inflammatory lesion

Abstract: A case is presented in which an anatomical feature, canalis sinuosus, manifested as a periapical radiolucency on an upper canine. This may have been interpreted as an inflammatory lesion and led to the patient receiving inappropriate treatment had a further radiograph not been taken. The incisive foramen and mental foramen are well known anatomical features which may mimic periapical inflammatory lesions but it is less common for a neurovascular canal to manifest as a periapical radiolucency on an upper canine. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 6 publications
1
43
1
4
Order By: Relevance
“…Shelley et al11 reported a case in which a well-defined radiolucency simulating a pathologic lesion was recognized around the top-left canine apex. Further radiographs and detailed clinical examinations proved that it was a variation of the CS.…”
Section: Discussionmentioning
confidence: 99%
“…Shelley et al11 reported a case in which a well-defined radiolucency simulating a pathologic lesion was recognized around the top-left canine apex. Further radiographs and detailed clinical examinations proved that it was a variation of the CS.…”
Section: Discussionmentioning
confidence: 99%
“…It has been stated that the palate may be pierced by many small foramina and marked by pits for palatine glands (Warwick & Williams 1973). However, despite a few cases reported in the literature (Kohavi 1994;Shelley et al 1999;Temmerman et al 2011), the occurrence of anatomical variations involving AFP region with clinically relevant diameters and their association with bony canals that may contain major neurovascular content has not been systematically assessed.…”
Section: Discussionmentioning
confidence: 99%
“…This canal was named "canalis sinuosus" by Jones (1939), and this term was suggested due to its doubled curved course. Few subsequent authors have referred to this canal (Warwick & Williams 1973;Heasman 1984;Shelley et al 1999;Balaji 2007) and apparently not much attention has being given to this structure in recent literature. However, this is a rather wide canal and carries not only the ASA nerve which is a considerable nerve in diameter (McDaniel 1956) but also the ASA artery.…”
Section: Discussionmentioning
confidence: 99%
“…& ZÚÑIGA, J. R It is also associated with complications by direct or indirect injury to the anterior superior alveolar neurovascular bundle, such as intraoperative bleeding, changes in the overall sensitivity of the territory of ASAN, and difficulty in osseointegration of implants (Arruda et al, 2017). For example, Shelley et al (1999) reported a case in which an abnormal extension of this canal was mistaken for a periapical lesion on an intraoral x-ray. Vâlcu et al reported the anatomic variation of a canal in the hard palate that was interpreted as a possible aberrant fissure of the maxilla, but may have been an anatomic variation of the CS.…”
Section: Pathwaymentioning
confidence: 99%